Kajian Faktor yang Memengaruhi Efisiensi Teknis Perkebunan Kelapa Sawit Rakyat di Kecamatan Bandar Pulau Kabupaten Asahan Propinsi Sumatera Utara - Simatupang, Jones T.; Siregar, M. Akbar; Sibuea, Mhd. Buhari (Universitas Galuh, 2025)
The technical efficiency of smallholder oil palm plantations is a reflection of the farmers' ability to coordinate the use of inputs to obtain the desired output. This study aims to determine the value of technical efficiency and factors that influence the technical efficiency of smallholder oil palm plantations. The research area was determined purposively on the grounds that it is a sub-district area that has the largest area of smallholder oil palm plantations in Asahan Regency as the regency area that has the largest area of oil palm plantations in North Sumatra Province. The research sample was determined by quota sampling of 150 samples originating from two villages, namely Gonting Malaha Village and Padang Pulau Village, each with 75 samples. The data analysis method used Data Envelopment Analysis and Censored Tobit Regression Analysis for data on the management of smallholder oil palm plantations during 2023. From the results of the study, it was found that the majority (81.33%) of smallholder oil palm plantations were not technically efficient, with an average technical efficiency value of 0.9782. Factors that significantly influence technical efficiency are gender, age, farming experience, number of productive crops cultivated, distance from the farmer's residence to the input market, farmer experience applying organic fertilizer, experience participating in farmer organizations, and experience using information and technology facilities related to farm management. Meanwhile, factors such as education level, family size, type of seed used, and access to credit by farmers have no significant effect on technical efficiency.